2017
DOI: 10.1007/s12072-017-9794-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic hepatitis C genotype 3 with Sofosbuvir-based therpy: a real-life study

Abstract: Both dual and triple therapy regimes resulted in SVR rates of >95% in CHC genotype 3 who were naive non-cirrhotics. However, the SVR rates were low in treatment-experienced cirrhotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…We previously reported an SVR (24 weeks) rate of 64% in patients treated with peginterferon and ribavirin in combination . In this present study, overall SVR12 was 95.9% (470/490), which is similar to those reported previously from other studies performed in the Indian subcontinent . Prior multicenter studies evaluating the efficacy of branded DAA have reported similar high SVR12 rates .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We previously reported an SVR (24 weeks) rate of 64% in patients treated with peginterferon and ribavirin in combination . In this present study, overall SVR12 was 95.9% (470/490), which is similar to those reported previously from other studies performed in the Indian subcontinent . Prior multicenter studies evaluating the efficacy of branded DAA have reported similar high SVR12 rates .…”
Section: Discussionsupporting
confidence: 91%
“…15 In this present study, overall SVR12 was 95.9% (470/490), which is similar to those reported previously from other studies performed in the Indian subcontinent. [16][17][18] Prior multicenter studies evaluating the efficacy of branded DAA have reported similar high SVR12 rates. [5][6][7]19 Our study supports the fact that generic DAAs are associated with high efficacy.…”
Section: Adverse Eventsmentioning
confidence: 93%
“…For patients treated with 24 weeks of SOF+RBV, AE data were available in 1346 patients from two studies. 36 38 The most common AEs were anaemia (28.1%, 95% CI 25.2% to 31.2%), headache (23.5%, 95% CI 14.5% to 35.8%), fatigue (22.9%, 95% CI 13.1% to 37.1%), myalgia (11.0%, 95% CI 8.6% to 14.1%), and insomnia (7.8%, 95% CI 5.2% to 11.5%).…”
Section: Resultsmentioning
confidence: 99%
“…The price of treatment remains a major barrier to curing hepatitis C for millions of people, and where rationing of treatment, lack of health insurance or lack of a national treatment program deny access to these drugs, people are turning to internet-based community portals or 'buyer's clubs' to obtain generic versions of direct-acting antivirals. [20][21][22][23] Freeman et al 23 showed very high cure rates when using…”
Section: Cost Evaluation Of Daasmentioning
confidence: 99%